2015
DOI: 10.1182/blood.v126.23.4997.4997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Genomic Rearrangements Associated with the Ex Vivo Resistance to Anthracyclines in Childhood Acute Leukemias

Abstract: INTRODUCTION: Resistance to drugs is connected with several genomic changes, but the major mutations are still unknown. Daunorubicin (DNR), idarubicin (IDA), doxorubicin (DOX) and mitoxantrone (MIT) are chemotherapeutics of the anthracycline family that are commonly used to treat acute leukemias (AL). OBJECTIVE: The aim of the study was to identify changes on the genome level and compare them with ex vivo resistance to DNR, IDA, DOX and MIT among children diagnosed with acute lymphoblastic (ALL) or myeloblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2 G). Integrins are known to participate in cell adhesion as well as cell-surface-mediated signaling [ 49 ]. We found that the expression of ITGA2, ITGA7, ITGB3, and ITGB5 increased significantly in treatment-naive PV patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 G). Integrins are known to participate in cell adhesion as well as cell-surface-mediated signaling [ 49 ]. We found that the expression of ITGA2, ITGA7, ITGB3, and ITGB5 increased significantly in treatment-naive PV patients (Fig.…”
Section: Resultsmentioning
confidence: 99%